Enhanced hydrogen evolution reaction of MoOx/Mo cathode by loading small amount of Pt nanoparticles in alkaline solution. (6th July 2017) - Jian, Chuanyong; Cai, Qian; Hong, Wenting; Li, Jing; Liu, Wei
Abstract: A simple approach for the synthesis of oxygen vacancy rich molybdenum oxide (MoO x ) on Mo foil using simple anodization method has been developed. The oxygen vacancy of synthesized MoO x is confirmed by Raman, XPS, and XRD measurements. MoO x /Mo electrode exhibits high active for hydrogen evolution reaction (HER) in alkaline solution. The HER performance of MoO x /Mo can be further improved by electrodepositing of small amount of Pt nanoparticles on MoO x . Pt-MoO x /Mo electrode shows high HER performance, which is close to the performance of Pt. Importantly, Pt-MoO x /Mo electrode has excellent stability even after 2000 potential cycles in alkaline solution. Our study proposed a simple method for preparing low-cost Mo based electrode for high efficient hydrogen production. Graphical abstract: Highlights: Oxygen vacancy rich molybdenum oxide (MoO x ) is synthesized on Mo foil using anodization method. MoO x /Mo exhibits high active and stable for hydrogen evolution reaction (HER) in alkaline conditions. The HER performance of MoO x /Mo can be improved by loading small amount of Pt nanoparticles. Pt-MoO x /Mo electrode has excellent HER performance and stability.